Burgenland or West-Hungary: The aspirations and limits of Austrian and Hungarian geography, 1918–1938. (July 2022) - Győri, Róbert; Jankó, Ferenc
Abstract: At the end of World War I, peace treaties wiped the Austro-Hungarian Empire off the map, and as a result of the Treaty of Trianon on June 4, 1920, the Kingdom of Hungary was dismembered. As a part of this process, a thin band of mainly German-speaking territory of some 4000 km 2, West-Hungary, became a part of Austria. This paper investigates both the arguments used by Hungarian geographers in defence of that country's territorial unity, notably those aimed at retaining and potentially recovering West-Hungary, and the arguments used by Austrian and German geographers to justify the annexation of that area. Analysing published and unpublished sources (articles, books, maps, propaganda material, and popular science literature), we show that scholars from both sides of the new border based their detailed arguments on similar theories, and used the same methods and mapping technologies for their own causes. We demonstrate that geographical arguments and analyses cannot be divorced from their political context, and that the politics of the new Europe that emerged after 1918 were profoundly geographical in nature. Highlights: Geographers were involved in the delimitation of new political boundaries after WWI. Hungarian geographers argued for the territorial integrity of Hungary. Geographical knowledge was fundamental to the building of identity in Burgenland. Austrian and Hungarian scholars based their argument on similar theories. Geographical arguments cannot be divorced from their political context.